Business operations of agrodealers and their participation in the loan market in Nigeria - Olomola, Aderibigbe (International Food Policy Research Institute, 2014)
This study employs primary data collected through structured questionnaires from 300 agrodealers and uses a Tobit type-II model for the analysis. The results show that interest rate, debt, value of asset, membership of trading association, and source of credit are major determinants of loan demand. Agrodealers need to organize themselves into input trading associations to enhance their creditworthiness and to unleash the inherent social capital and information advantages for improved agrodealership financing.